Educational and learning resources for gifted and talented people: perspective of professional women from Argentina - Irueste, Paula (2024)
Fil: Irueste, Paula. Universidad Nacional de Córdoba. Facultad de Psicología. Cátedra Psicología Clínica; Argentina.